The Role of Individual Performance in the Influence of Innovation Culture and Quality of Work Life On Competitive Advantage - ., Nurlaila; Ratnasari, Sri Langgeng; Harsasi, Meirani; Sultan , Zulkifli (Journal of Ecohumanism, 2024)
Providing empirical evidence of the role of individual performance on the influence of innovation culture and quality of work life to increase competitive advantage is the aim of this study. This study takes the tourism sector as an object with SME employee respondents working in the tourism sector, such as travel agents, hotels, tourist attractions, restaurants, transportation, souvenir shops, etc. in the Jakarta area, Indonesia. On the basis of convenience sample selection, 528 respondents were obtained. The analysis tool in this study uses SEM-PLS. The research results show that individual performance plays a mediating role in the influence of innovation culture and quality of work life on competitive advantage. The theoretical implication of this research is to strengthen contingency theory, which is associated with competitive advantage, individual performance, innovation culture, and quality of work life. The practical implication of this study is the importance of a culture of innovation, quality of work life and individual performance to increase competitive advantage in the SME tourism sector so that they are able to win business competition and maintain the sustainability of the SME business.